PRODUCTION AND MARKETING OF SUGARCANE IN VISAKHAPATNAM DISTRICT OF ANDHRA PRADESH - R. ASHA*, G. SUNIL KUMAR BABU and T. SURYA TEJA, (The Journal of Research ANGRAU, 2019)
The production and marketing of sugarcane cultivation have been studied in Visakhapatnam district ofAndhra Pradesh during 2018-19. The results revealed that cost of cultivation was high for plant crop than theratoon farming with the benefit-cost ratio of 1.10 for plant crop and 1.30 for ratoon crop. Net income for the plantcrop was Rs.34735/- and Rs.41898/- for the ratoon. The coefficients human labour (0.73), manure (0.25) andseed rate (0.39) were showing positive significant effect on output and plant protection chemicals (-0.08)showing negative significant effect on output. The price spread analysis for the selected channel indicated thatthe producer received 70.83 per cent of consumer’s price in channel 1 (sugar), 81.43% in channel 2 (jaggery).Total marketing cost was highest for channel 1 (34.30%) than the channel 2 (18.80%). The index of marketingefficiency was high for channel 2 i.e. 3.33 as compared to 1.06 for channel 1.